2012
DOI: 10.1002/emmm.201100604
|View full text |Cite
|
Sign up to set email alerts
|

Genetic partitioning of interleukin‐6 signalling in mice dissociates Stat3 from Smad3‐mediated lung fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a fatal disease that is unresponsive to current therapies and characterized by excessive collagen deposition and subsequent fibrosis. While inflammatory cytokines, including interleukin (IL)-6, are elevated in IPF, the molecular mechanisms that underlie this disease are incompletely understood, although the development of fibrosis is believed to depend on canonical transforming growth factor (TGF)-β signalling. We examined bleomycin-induced inflammation and fibrosis in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
118
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(123 citation statements)
references
References 54 publications
5
118
0
Order By: Relevance
“…Activation of STAT3, AKT, and Wnt/ b-catenin pathways was also reported in mouse models of lung fibrosis (59,60). STAT3 activity is directly correlated to inflammatory infiltrates in the lungs and with the severity of fibrosis (61). In our model, thickening of lung connective tissue, collagen content, and alveolar luminal narrowing, all of which are histological features of lung fibrosis, are diminished by niclosamide in HOCl-mice.…”
Section: Discussionsupporting
confidence: 78%
“…Activation of STAT3, AKT, and Wnt/ b-catenin pathways was also reported in mouse models of lung fibrosis (59,60). STAT3 activity is directly correlated to inflammatory infiltrates in the lungs and with the severity of fibrosis (61). In our model, thickening of lung connective tissue, collagen content, and alveolar luminal narrowing, all of which are histological features of lung fibrosis, are diminished by niclosamide in HOCl-mice.…”
Section: Discussionsupporting
confidence: 78%
“…Alternatively, the fibrosis observed in Fgf2 2/2 mice may develop through a different mechanism than that observed in wild-type mice. For example, IL-6 is known to directly stimulate fibrosis independently of TGF-b1 (60,61), and Fgf2 2/2 mice have prolonged IL-6 expression at late time points after bleomycin.…”
Section: Our Results Show That Fgf2mentioning
confidence: 99%
“…Although IL-6 trans signaling is known to cause fibrosis, the underlying molecular mechanism is unknown. In a mouse model of fibrosis, it was shown that hyperactivation of STAT3 enhanced fibrosis (14), and excessive activation of STAT3 was found in the lung tissue of patients with idiopathic lung fibrosis. Consistent with a role of STAT3 in mediating fibrosis, keloid fibroblasts have excessive IL-6 secretion and respond to IL-6 stimulation with up-regulation of collagen transcription (15).…”
mentioning
confidence: 99%